The negative thoughts workbook : CBT skills to overcome the repetitive worry, shame, and rumination that drive anxiety and depression - Clark, David A., 1954- (New Harbinger Publications, Inc., 2020)
"Emotional distress takes many forms-such as excessive worry, rumination, regret, shame, humiliation, or resentment. Managing these negative thoughts is essential for emotional healing and wholeness. In this workbook, renowned psychologist David A. Clark offers a transdiagnostic, cognitive behavioral approach to effectively target these unwanted thoughts. Using practical, step-by-step instructions and activities, readers will learn to free themselves from the addictive thought patterns that trap them in an endless cycle of negativity"--